WINTER-SPRING PRECIPITATION AS THE PRINCIPAL CONTROL ON PREDOMINANCE OF C3 PLANTS IN CENTRAL ASIA OVER THE PAST 1.77 MYR: EVIDENCE FROM δ13C OF LOESS ORGANIC MATTER IN TAJIKISTAN - Yang S.; Ding Z. (My University, 2006)
Although changes in atmospheric CO2 levels are thought to be the major factor driving long-term C3/C4 vegetation evolution, recent studies tend to emphasize the effect of regional climate conditions on C3/C4 variations. The middle latitudes (30-45°), in which C3/C4 plants are highly sensitive to environmental changes, provide an optimal basis for the investigation of the relative impacts of climate and pCO2 on shifts in C3/C4 cover. In order to assess the factors controlling these shifts as well as the complex interactions between environmental factors, the carbon isotopic composition of bulk organic matter from the Chashmanigar loess section (southern Tajikistan) was measured for the past 1.77 Myr. In general, the δ13C record shows mostly negative values throughout the sequence, almost all δ13C values falling between - 23‰ and - 26‰, indicating a predominance of C3 plants in Central Asia over this time period, despite the presence of numerous glacial-interglacial cycles. From 0.85 Myr to the present, the δ13C values become increasingly positive, reflecting a growing C4 signal. However, this C4 component is not detectable prior to 0.25 Myr, after which minor peaks are evident at ~ 228, ~ 171 and ~ 18 kyr. The δ13C record from Chashmanigar indicates that winter-spring precipitation, i.e., Mediterranean climatic conditions, have characterized Central Asia throughout the past 1.77 Myr, leading to the predominance of C3 vegetation. In the context of glacial-interglacial-scale changes in atmospheric CO2, therefore, it is climate rather than pCO2 that controls C3/C4 variations in Asia's middle latitudes. The gradual increase in the C4 component since 0.85 Myr, especially the notable peaks after 0.25 Myr, may have been caused by an increase in summer precipitation due to an enhanced southward shift of the climate zones. © 2005 Elsevier B.V. All rights reserved.
Keywords: C3 AND C4 PLANTS; CARBON ISOTOPES OF ORGANIC MATTER; CENTRAL ASIA; CLIMATE ZONES; LOESS; PRECIPITATION SEASONALITY